Development of Mechanistic Shrinkage Cracking Model for Cementitiously Stabilized Materials. Issue 1 (2016) - Wang, Jingan; Wen, Haifang; Muhunthan, Balasingam
Transverse and block cracking have been identified as the most severe distresses for pavements with cementitiously stabilized layers (CSLs). Such cracking results from shrinkage, especially drying shrinkage, of the CSL. This study identified the properties of cementitiously stabilized materials that significantly affected shrinkage cracking in pavements with CSLs, including ultimate drying shrinkage, gradient drying shrinkage, and the coefficient of friction. Laboratory experiments were conducted to quantify these properties. Empirical models to predict the ultimate drying shrinkage and gradient drying shrinkage were developed. In addition, restrained drying shrinkage tests were developed to simulate field shrinkage cracking. These test results, which considered the effects of moisture and drying shrinkage gradients throughout the depth of the CSL, were used to develop new mechanics-based models for shrinkage crack spacing and width. The new models were shown to provide reasonable predictions of shrinkage crack spacing and width observed in laboratory tests.